Pengaruh Penggunaan Media Audio Visual Dan Peran Orang Tua Terhadap Minat Belajar Pendidikan Agama Kristen Sekolah Dasar Di Tapanuli Selatan T.A 2025/2026 - Hutapea, Lidia Kando; Sitompul, Baginda; Simanullang, Pardomuan (Journal of Innovative and Creativity, 2026)
This study aims to analyze the influence of the use of audio-visual media and parental involvement on students’ interest in learning Christian Religious Education (CRE) at an elementary school in South Tapanuli Regency in the 2025/2026 Academic Year. The background of this study is the low level of students’ interest in learning CRE, which is indicated by limited attention, participation, and enthusiasm during the learning process. The less optimal use of instructional media and insufficient parental involvement are assumed to be contributing factors to this condition. This research employed a quantitative approach using a survey method. The population consisted of fifth-grade elementary school students, with a total sample of 36 students. Data were collected using a closed-ended questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression to determine the partial and simultaneous effects of audio-visual media use (X1) and parental involvement (X2) on students’ learning interest in CRE (Y). The results show that there is a positive and significant influence of the use of audio-visual media on students’ learning interest in CRE. Likewise, parental involvement has a positive and significant effect on students’ learning interest. Simultaneously, the use of audio-visual media and parental involvement contribute significantly to the improvement of students’ learning interest in CRE, as indicated by the coefficient of determination, which falls into the strong category. In conclusion, the more effective the use of audio-visual media in classroom instruction and the higher the level of parental involvement in supporting learning activities at home, the greater the students’ interest in learning Christian Religious Education. This study recommends enhancing innovative instructional media utilization and strengthening collaboration between schools and parents to improve the quality of CRE learning at the elementary school level